ARCHAEOLOGICAL EXCAVATIONS IN STATE DEPOSITS OF WALLED ASSEMBLY XLLANGCHIC-AN (EX UHLE) - CHAN CHAN ARCHAEOLOGICAL COMPLEX - Dávalos García, José Luis (2015)
This is a tentative study containing data collected and compiled as a result of archaeological excavations that were developed in the field of Joint Walled compoundXllangchic-An deposits-an, framed in the “Project of Archaeological Research and Conservation Area and Perimeter Walls Deposits in the western sector of the Joint Walled Xllangchic-An (ex Uhle) Chan Chan Archaeological Complex “implemented from 15 April 2012 until 15 March 2013 as the industry-an los depósitos of Xllangchic-An , were operated archaeologically first by us, our commitment and responsibility to the archaeological monument was higher; for which reason we should develop the intervention in the context of the paradigm of “minimal intervention and maxima authentication” as well as respecting in the Master Plan for the Conservation and Management of the Chan Chan Archaeological Complex. Arqueológica in literature about the role of these conflicting proposals estructurases theme, according to some term context: warehouses, depots and qollcas (Quechua term that refers to the structures used as deposits incanato). In mind the context of the project, we will use the term deposits. In relation to the issue of the functionality of deposits, our conclusions and discussions will be developed based on the results obtained after a basic evaluation of the retrieved deposits contents, which were documented with the process of screening the material extracted in excavations. This allows us a basis for interpretation of the data based on the intervention area online, and on this basis, then proceed to cross the information with the results obtained in other archaeological projects that have developed the same line of research, in order to obtain more information to allow us to specify more precisely our problem.